2419. Standard vs. Alternative Therapy for Stenotrophomonas maltophilia Infections: Focus on Trimethoprim–Sulfamethoxazole, Minocycline, and Moxifloxacin Monotherapy. (26th November 2018) - Badwal, Jasmin; Traugott, Kristi; Hand, Elizabeth
Abstract: Background: Stenotrophomonas maltophilia is a Gram-negative bacilli associated with nosocomial infections. TMP-SMX is often considered the first-line agent; however, use may be limited due to adverse effects or resistance. Both minocycline and moxifloxacin have historically been used based on in vitro data; however, there are limited studies assessing clinical outcomes. The purpose of this study was to compare the efficacy of TMP-SMX, minocycline, or moxifloxacin monotherapy for treatment of S. maltophilia infections. Methods: This was a single-center, retrospective chart review from January 2006 to September 2017. Subjects were selected by cross-referencing pharmacy billing and culture data. Patients ≥18 years of age were included if they had isolated S. maltophilia in at least one culture and were treated for at least five days. Patients were excluded due to pregnancy, incarceration, cystic fibrosis, receipt of combination therapy, or having prior case of treated S. maltophilia infection. Complete success was defined as meeting all three of the following: (1) resolution of signs/symptoms, (2) no repeat isolation 30 days after end of therapy, and (3) no switch or addition of alternative agents that cover S. maltophilia . Partial success was defined as meeting at least two out of the three criteria. Results: A total of 109 patients were included in this study. No statistically significant difference in complete clinical success achievement was identified: TMP-SMX 14/32 (43.8%) vs. minocycline 17/37 (45.9%) vs. moxifloxacin 16/40 (40%), P = 0.8674. There was also no significant difference when including those that achieved partial clinical success: TMP-SMX 29/32 (90.6%) vs. minocycline 35/37 (94.6%) vs. moxifloxacin 34/40 (85%), P = 0.3724. Moxifloxacin use was associated with a significantly longer median LOS of 41.5 days compared with 24.5 days for TMP-SMX and 10 days for minocycline ( P = 0.0340). Resistance development within 30 days post-treatment only occurred in 4 patients who received moxifloxacin ( P = 0.0258). There was no difference in mortality nor treatment duration. Conclusion: Clinical success achievement was found to be similar in patients treated with TMP-SMX, minocycline, or moxifloxacin monotherapy for S. maltophilia infections. Disclosures: All Authors: No reported disclosures.